Analisis Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Kelurahan Jatimulya Periode Febuari 2022 - Juni 2022 - Rukiyah, Sri; Waluya, Sri; Rachmawati, Budi (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
A company can progress or be destroyed due to the quality and behavior of the people in the company. Jatimulya village is an institution in the field of government, which is tasked with carrying out part of the government's authority which includes the fields of government, economy, development and people's welfare. The purpose of this study was to determine how much influence motivation and work discipline have on performance at the Jatimulya Village Office. motivation is a driving force in individuals to carry out certain activities in achieving goals by providing the right motivation, employees will be encouraged to do as much as possible in carrying out their duties and they believe that with the success of the organization in achieving its goals and objectives. work discipline is the attitude or behavior of someone who obeys the rules and norms that apply and consciously obeys all regulations as well as their duties and responsibilities. performance is linking work results with employee behavior. As a behavior, performance is an employee activity directed at carrying out the organizational tasks assigned to each employee. to determine which samples will be used as respondents / data sources, the most appropriate sampling (appropriate) uses an area sample technique of 35 people to conduct research. The result of the t test analysis (X1) is 1.862 which is smaller than the table value of 2.030. Then H0 is accepted and H1 is rejected, which means that work motivation has a positive and significant effect on employee performance. This states that if work motivation on employee performance is getting better, then their performance will also increase. The result of the t test analysis (X2) is 5.103 which is greater than the t table value of 2.030. Then H0 is rejected and H2 is accepted, which means that Work Discipline has a significant effect on Employee Performance. This states that if employee work discipline is getting better, then their performance will also increase. The results of the calculation of multiple linear regression analysis provide the results that, the variables of motivation (X1) and work discipline (X2) have a unidirectional relationship with employee performance (Y) at the Jatimulya Village Office, obtained a value of Y 5.110 + 0.227X1 + 0.638X2 which means that work discipline has a significant influence on employee performance. Simultaneously Motivation and Work Discipline have a positive and significant effect on Employee Performance at the Jatimulya Village Office. This can be proven by the significance value of the F test below 0.05, which means that the independent variable simultaneously affects the dependent variable. The coefficient of determination test of employee performance is 58.7% as indicated by the amount of R squer of 58.7% while the remaining 41.3% is influenced by other factors that are not included in the research model.